Exploring Insect-based technology for waste management and livestock feeding in selected South and East Asian countries - Salam, Muhammad; Zheng, Longyu; Shi, Dezhi; Huaili, Zheng; Vambol, Viola; Chia, Shaphan Yong; Hossain, Md. Nuralam; Mansour, Abdelaziz; Eliw, Moataz; Dong, Mengyao; shazadi, Amina; Ullah, Ehsan (Environmental technology & innovation, 2023)
This paper aimed to investigate the Asian’s willingness to use black soldier fly larvae for organic waste management and livestock feed. A random sampling method was adopted based on waste generation and substrate availability. In addition, it contributes to filling gaps in research into public acceptance, social perception, and Attitude towards BSFL-based organic waste management. It has been found that different subgroups in different countries have inconsistent attitudes towards using BSFL technology. Stack group in Afghanistan (3.94 ± 0.90), Pakistan (4.45 ± 0.61), China (4.48 ± 0.54) highly agree, and Bangladesh (3.21 ± 0.57) agree, but the other groups are not sure or show different perceptions. The results of our study indicate that BSFL is a more acceptable feed supplement than conventional food; participants rated their willingness to blend 500 grams of BSFL with conventional feed and preferred to feed livestock, dogs, fish, birds, and cats. It is established that most of the respondents were familiar with the BSFL technology, namely in China (3.58 ± 0.87), Bangladesh (3.55 ± 0.8), Pakistan (3.24 ± 0.82), Afghanistan (2.63 ± 0.5). The waste group with the mean value from Afghanistan (2.87 ± 0.76), Bangladesh (2.74 ± 1.41), China (2.76 ± 1.12), and Pakistan (2.78 ± 1.28). Finally, the article shows a direct relationship between public acceptance of BSFL for waste management and subject erudition. [Display omitted] •Environmental friendliness and the usefulness of BSFL as a feed for livestock are recognized In Asian countries, public acceptance of the BSFL as livestock feed is controversial.•The higher the subject erudition, the higher the willingness to use BSFL as livestock.•BSFL-based waste management strategy on market systems needs to be studied.